Novel methods to determine hydrothermal residual stresses in fiber-reinforced polymer composite - John Wang; Paul W. Adcock; Wing Kong Chiu (Academia Materials Science)
Unidirectional (UD) and unbalanced carbon-epoxy laminates were conditioned under various temperature and humidity conditions. Hydrothermal strains in these laminates manifested as linear dimensional and curvature changes, respectively. Through nondestructive measurements of these changes, the relationship between residual stress in a composite material and its exposure to moisture and thermal conditions was established. Furthermore, novel investigations were undertaken using unbalanced laminates to determine the relaxation of residual stresses under fatigue loading and to measure the residual stresses through direct force measurement using a four-point bend test. The results indicated that the offset effect of hydro and thermal conditions on residual stress is significant, even though it is often ignored in design practice. In the UD and unbalanced laminates, under conditions corresponding to a typical operational moisture content (0.5% moisture content), up to 35% and 38% of thermal residual stress is offset, respectively. The fatigue test, with a tensile peak load of 2,000 µε, showed significant decrease in residual stress. An average decrease of 17.3% occurred after the first cycle, with the total decrease reaching 33.8% after 30,000 cycles. The residual stress relaxation could have a significant impact on fatigue life predictions of composite structures. A four-point bend test was used to determine the load required to flatten unbalanced laminates. A finite element analysis concurred with the experimental results, and a symmetrical model of a balanced laminate was further used to calculate residual strains. Residual strains of −221 µε and 3,192 µε were found in the longitudinal and transverse direction plies, respectively.